GAMIFIKASI DALAM PENDIDIKAN INTEGRITAS: MEMBANGUN BUDAYA ANTIKORUPSI DI KALANGAN PELAJAR SMA - Sari, Wulan Purnama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
The increasing prevalence of corruption cases in Indonesia demands innovative educational approaches to instill integrity values from an early age. This Community Service Program aims to build anti-corruption awareness among high school students through gamification using the online game Corruzione. The game provides a daily decision-making simulation that requires players to choose between honest and corrupt actions and face the consequences of their choices. The activity was conducted at Bunda Hati Kudus Senior High School Jakarta involving 23 students from class XI-2A. The program included interactive material delivery, group discussions, educational video screenings, and Corruzione online game session as the main learning media. The results indicate that gamification effectively enhances participants’ understanding of various forms of corruption, including dishonest practices commonly found in school environments, such as proxy attendance and task manipulation. The hands-on gaming experience creates strong emotional and cognitive impacts, facilitating the internalization of anti-corruption values. Furthermore, students demonstrated increased critical thinking and ethical awareness when confronting moral dilemmas simulated in the game. This activity proves that game-based learning media not only align with the characteristics of today’s students but also serve as a strategic alternative to strengthen character education and foster an anti-corruption culture within educational settings. Thus, gamification can be an innovative solution for early preventive efforts against corruption.